Independence or interdependence: The role of artificial intelligence in corporate entry mode for overseas energy investments - Wei Liu; Mengxiao Cao; Jianwen Zheng; Zuopeng Zhang (Journal of Innovation & Knowledge (JIK), 2024)
Artificial intelligence (AI) technology has significantly transformed corporate behavior in the energy sector by enhancing the capacity and efficiency of information transmission and big data analysis. However, there is still a limited understanding of how AI influences new market entry mode strategies in overseas energy investments. Drawing on information processing theory, we propose that firms with advanced AI technology exhibit superior data processing capabilities, which can help energy companies mitigate the uncertainties associated with entering a foreign market and encourage them to choose a wholly-owned entry mode. We further hypothesize that the state ownership of firms, the political affinity between home and host countries, and the risk preferences of firm executives serve as moderating factors. Using a sample of Chinese-listed multinational firms in the energy sector from 2010 to 2021, our empirical results strongly support these predictions. These findings contribute to the emerging and crucial literature on the impact of AI technology on firms' overseas investment behavior, particularly in the energy sector.
Keywords: F23; O33; Q43; 650; Artificial intelligence; Energy investments; Entry mode; State ownership; Political affinity; Risk preferences